A compilation of miniature models and doll-house making technique - Sipaco, Daisy Anne Cuison
This is a very timely research study because at present more and more designs are becoming harder to execute because of innovativeness. Knowing the basics of model constructing will assist the designer a great deal because he can add or take away from the basics. Many procedures are mentioned here to facilitate knowledge of model-making. From exterior to interior structures this research study will at least, in any way, help in constructing appropriate models for effective presentation. Materials and procedures are made clear and understandable for convenient, time-saving, and most of all cost-saving construction of models. Although other materials of high-cost because of their customized are recommendable for easier construction.